2021
DOI: 10.1097/hjh.0000000000002752
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the ascending aorta dilatation in patients with arterial hypertension

Abstract: Background: Ascending aorta (ASC) dilatation (AAD) is a common finding in arterial hypertension, affecting about 15% of hypertensive patients. AAD is associated with an increase in cardiac and vascular hypertension-related organ damage, but its prognostic role is unknown. The aim of the study was to evaluate the prognostic value of AAD as predictor of cardiovascular events in essential hypertensive patients.Methods: Recruited patients underwent two-dimensional transthoracic echocardiography from 2007 to 2013 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Therefore, 190 studies were reviewed; of these, 101 did not report data on incident non-fatal or fatal cardiovascular events or all-cause mortality and 41 on AR diameter or ascending aorta data, 33 were review, commentary, editorial articles, and 6 were excluded for miscellaneous reasons. A total of 9 studies, including participants without underlying known aortic pathologies (i.e., aneurysms) or connective diseases and containing sufficient clinical and cardiac imaging data, were included in the final review (17)(18)(19)(20)(21)(22)(23)(24)(25) (Figure 1). The Newcastle-Ottawa Score, used for assessing the quality of the studies, ranged from 7 to 9, and the mean score was 7.8.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, 190 studies were reviewed; of these, 101 did not report data on incident non-fatal or fatal cardiovascular events or all-cause mortality and 41 on AR diameter or ascending aorta data, 33 were review, commentary, editorial articles, and 6 were excluded for miscellaneous reasons. A total of 9 studies, including participants without underlying known aortic pathologies (i.e., aneurysms) or connective diseases and containing sufficient clinical and cardiac imaging data, were included in the final review (17)(18)(19)(20)(21)(22)(23)(24)(25) (Figure 1). The Newcastle-Ottawa Score, used for assessing the quality of the studies, ranged from 7 to 9, and the mean score was 7.8.…”
Section: Resultsmentioning
confidence: 99%
“…This was not the case, however, in the PAMELA study in which the association of AR diameter with incident cardiovascular events lost its significance when LV mass index was included in the multivariate analysis (21). Studies targeting ascending aortic diameter (19,23,25) showed non-univocal findings. Among the participants from the Framingham offspring and third-generation cohorts, the enlarged ascending aorta was not significantly associated with cardiovascular events (23).…”
Section: Non-fatal and Fatal Cardiovascular Eventsmentioning
confidence: 96%
See 2 more Smart Citations
“…The findings in favour of the independent value of aortic root in predicting cardiovascular outcomes is based on few prospective studies performed in northern American and European population-based samples as well as in hypertensive cohorts [11][12][13][14][15]. The Cardiovascular Health Study, including 3993 elderly without overt cardiovascular disease at baseline from a bi-racial sample of the general population, was the first to open this line of research [11].…”
mentioning
confidence: 99%